Analisis Faktor Penempatan dan Penentu Keberhasilan Praktik Kerja Lapangan (PKL) Menggunakan Metode Kuantitatif Deskriptif (Studi Pada SMK PGRI 3 Malang) - Abdurrahman Firmansyah; Retno Indah Rokhmawati; Satrio Agung Wicaksono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
This research describes the perceptions between students, teachers and the Business World / Industrial World in determining the success of field work practice programs (PKL) for SMK PGRI 3 Malang students. The analysis is known from the placement factors and determinants of the success of street vendors in SMK PGRI 3 Malang. The results of the analysis are then submitted as input for further PKL activities. This research was carried out in Malang PGRI 3 Vocational High School of Software Engineering (RPL), Computer and Network Engineering (TKJ), and Multimedia (MM) expertise. The respondents of this study were 110 students, 9 PKL supervisors, and 5 companies (DU / DI). This research uses descriptive quantitative methods, data collection using questionnaires, and interviews. The research resulted in placement factors and determinants of the PKL success of SMK PGRI 3 Malang students as a whole include: academics included in the neutral category. Student readiness, student residence, benefits of street vendors, street vendors constraints, facilities, students' perceptions of teacher competence, and student performance are included in the high category.